Public Expenditure Reform The Health Care Sector in the United Kingdom - Koen, Vincent (OECD Economics Department Working Papers, 2000)
Health services are largely tax-financed in the United Kingdom and account for 14 per cent of general government spending. This paper analyses how the National Health Service (NHS) has been dealing with the associated expenditure pressures in the pre-1990 set-up and during the "quasi-market" years and how it is to cope with them under the "co-operative" arrangements put in place since 1997. While the budget constraint was traditionally tight in the NHS, leading to pervasive rationing and queuing as well as diversion towards the private sector, it has been relaxed somewhat with the budgetary boost announced by the Government in March 2000. The challenge is now to make the best use of the new-found financial room for improvement ...